Emissões de gases de efeito estufa da mobilidade urbana: o caso de Natal - Toledo, André Luiz Lopes (2019)
This study aims to identify the status of greenhouse gas (GHG) emissions from urban transport of a medium size city in Brazil - Natal / RN - identifying subsectors with the highest emissions and presenting proposals for mitigation of GHG emissions and of air pollutants, through mitigation scenarios and public policy proposals. Based on data from urban road and rail mobility and the Urban Mobility Plan (PlanMob) of the City of Natal, based on the methodology of the Global Protocol for Greenhouse Gas Emissions Inventory of Community Scale (GPC) of the Intergovernmental Panel on Changes (IPCC) and the creation of scenarios for up to 10 subsequent years, it is possible to verify that individual motorized transport accounts for 60% of the total emissions of the urban transport sector, with the highest amount of equivalent emissions of carbon dioxide (CO2eq) per passenger between all forms of mobility. It was verified that the urban mobility planning of the municipal government (PlanMob) departs from the National Urban Mobility Policy (PNMU), substantially increasing GHG emissions in the scenarios considered for 2020 and 2025. Mitigation scenarios integrating electrified public transport and non-motorized transport solutions present a reduction of GHG emissions of around 5% and a reduction of 7.5% of Particulate Matter (PM) in 2025, in relation to the reference scenario. Data surveys and studies are suggested for the adoption of several other mitigation actions identified with a much more significant potential to reduce GHG emissions and urban air pollutants.